Comprehensive cardiac rehabilitation for patients following infective endocarditis: results of the randomized CopenHeartIE trial. (5th June 2021) - Rasmussen, Trine Bernholdt; Zwisler, Ann-Dorthe; Risom, Signe Stelling; Sibilitz, Kirstine Lærum; Christensen, Jan; Bundgaard, Henning; Moons, Philip; Thygesen, Lau Caspar; Lindschou, Jane; Norekvål, Tone Merete; Berg, Selina Kikkenborg
Abstract: Aims: Infective endocarditis is a complex and highly mortal disease requiring lengthy treatment. Physical and mental deconditioning is common. Nonetheless, rehabilitation is virtually unexplored in this population. The aim of this trial was therefore to investigate the effects of cardiac rehabilitation in patients following endocarditis. Methods and results: In a randomized trial, adults with left-sided or cardiac device endocarditis were randomized 1:1 to 12 weeks of physical exercise training and five psycho-educational consultations (cardiac rehabilitation) vs. usual care without rehabilitation (control). Primary outcome was mental health measured by SF-36 Mental Component Summary (MCS) at 6 months. Secondary outcome was physical capacity measured by peak oxygen uptake (VO2 ) at 4 months. Exploratory outcomes were investigated. Low inclusion rate resulted in trial termination before reaching the target sample size. A total of 117 participants (mean age: 60 years, 81% male) were randomized to cardiac rehabilitation ( n  = 58) or to control ( n  = 59). Mental health and physical capacity at baseline were generally poor (MCS: 38.9–42.2 points, VO2 peak: 16.1–16.6 mL/kg/min). Cardiac rehabilitation compared with control showed no effect on mental health (MCS: 44.6 points vs. 48.8 points, P  = 0.41) or physical capacity (VO2 peak: 19.9 mL/kg/min vs. 18.0 mL/kg/min, P  = 0.09). Effects favouring the intervention were identified in exploratory outcomes including general fatigue ( P  = 0.005), and physical capacity as maximal power (W) ( P  = 0.005). Adherence to the intervention was 28%. Conclusions: Results indicate no effect of cardiac rehabilitation in patients following endocarditis; however, lack of statistical power and poor adherence render findings inconclusive. Valuable insight into patients' capabilities and safety was gained, and further investigations into rehabilitation needs and modes of delivery in this high-need population should be a future priority. Registration: The trial is registered at ClinicalTrials.gov, NCT01512615